Coming Out of the Cave of Nationalism: A Bakhtinian Carnival Reading of the Epic Arab Shamo's Damdam Castle and the novel No Friend, Except Bahroz Buchani's Mountains - Saleh, Hersh Mohammed Saeed; Jaafar, Hamid Mustafa (Sulaimani Journal for Humanities, 2025)
Dogmatism and rigidity result from resisting and failing to adapt to the era and the rapid changes of the world. And what kind of world is this? A post-metaverse, post-artificial intelligence world. If such dogmatism and rigidity stem from nationalism and a singular mode of national politics—one that imposes an unequal and unjust stance toward other nations and lands (in this case, the Kurdish nation and Kurdistan)—then the catastrophic consequences will be far beyond a mere political issue; they will transform national reflection into an existential crisis rather than a normal or conventional concern. Breaking away from this dogmatism and finding an insightful, suitable alternative is the task of research and intellectual-literary critique. In this study, we attempt to identify one of these logical and realistic alternatives. Our research consists of: An introduction, The theoretical framework based on Mikhail Bakhtin’s carnival theory, which serves as the foundation and conceptual lens for analysing two literary works: The First section on The Fortress of Dimdim an epic by Arab Shamo and the second section on No Friend But the Mountains a novel by Behrouz Boochani, The final part of the study focuses on the conclusions and findings, examining the literary analysis of these two Kurdish works through the lens of Mikhail Bakhtin’s carnival theory.
Keywords: Nationalism; Bakhtin; Carnival; Castle of Dimdim; Shamo; No Friends; Boochani; Kurd; Kurdistan